Peran Peternak Perempuan Dalam Peternakan Sapi Potong Di Kabupaten Nagekeo - Kadju, Kristiana; Beli Moti, Klemens; Kia Pati , Nikolaus; K. Dheko, Liberius (Fakultas Pertanian dan Peternakan Universitas Muhammadiyah Bengkulu, 2025)
The aim of this research is to determine the characteristics of female breeders in raising beef cattle in Nagekeo Regency and the role of female breeders in beef cattle farming when viewed from the aspects of control, access and decision making. This research was carried out from April 1 to May 30 2025 in Nagekeo Regency. Data collection techniques in this research are observation and interviews. The research results show that there is very high involvement of women in the control and decision-making aspects. However, the aspect of access to information still needs to be improved. The conclusion of this research is: the role of female farmers in beef cattle farming in Nagekeo Regency in terms of access to information, control aspects and decision making is very involved in these activities.